Sosialisasi dan Pelatihan Penulisan Karya Ilmiah Bagi Siswa-Siswi SMAN 2 Situbondo - Nurul Avidhah Elhany; Desi Indriyani; Yasmini Suryaningsih; Ifoniyatul Fitriya; Rekso Sandany; Imdadir Rahman (Lembaga Penjaminan Mutu Universitas Abdurachman Saleh Situbondo, 2025)
Scientific paper is the result of a written work of an idea that has been validated through the research process. In creating a scientific paper, writing skills are needed which are the result of logical thinking and systematic. Currently, students must be masters of writing skills, especially high school students. However, in its application there are still several obstacles, because writing is not an easy thing to master, especially for high school students. To make high school students skilled in writing scientific papers, it is necessary to equip them with an understanding of good and correct writing methods and techniques through a Community Service activity. This activity aims to improve students' knowledge and skills in writing a scientific paper and contribute to the development of science in general. The students in this activity were 40 students of SMAN 2 Situbondo on September 10, 2024 using the counseling method with the stages of socialization and education, mentoring, and evaluation. In the implementation of this activity, students were very excited, especially during the discussion session and it was known several problems faced by students in writing scientific papers. However, through material sessions and mentoring, solutions have been obtained to overcome these obstacles. This can be seen from the level of satisfaction of participants in training activities, an average of 81.5% were very satisfied with all assessment indicators. Based on all the activities, it can be concluded that the participants have shown an improvement in compiling a scientific paper.